2016
DOI: 10.1021/acs.inorgchem.6b01207
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiproliferative Activity of [RuCp(PPh3)2(HdmoPTA)](OSO2CF3)2 (HdmoPTA = 3,7-H-3,7-Dimethyl-1,3,7-triaza-5-phosphabicyclo[3.3.1]nonane)

Abstract: The complex [RuCp(PPh3)2(HdmoPTA)](OSO2CF3)2 (2; HdmoPTA = 3,7-H-3,7-dimethyl-1,3,7-triaza-5-phosphabicyclo[3.3.1]nonane) was synthesized and characterized. Its crystal structure was determined by single-crystal X-ray diffraction. The complex showed a more potent antiproliferative activity than cisplatin against a representative panel of human cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 26 publications
8
35
0
Order By: Relevance
“…[48] The obtained GI 50 values, for the same panel of tumour cancer cells, which are given in Table 1, show that this compound displays a bigger antiproliferative activity than those for cisplatin and RAPTA complexes (in the range 0.17-0.29 μM). Nevertheless, in contrast with the first expectations, this complex showed a substantial enhancement of the antiproliferative activity with respect to the starting complex 55, constituting the first component of the so-called 2 nd generation of this family of complexes containing dmoPTA.…”
Section: Complexes With Hdmopta and Dmoptamentioning
confidence: 85%
See 1 more Smart Citation
“…[48] The obtained GI 50 values, for the same panel of tumour cancer cells, which are given in Table 1, show that this compound displays a bigger antiproliferative activity than those for cisplatin and RAPTA complexes (in the range 0.17-0.29 μM). Nevertheless, in contrast with the first expectations, this complex showed a substantial enhancement of the antiproliferative activity with respect to the starting complex 55, constituting the first component of the so-called 2 nd generation of this family of complexes containing dmoPTA.…”
Section: Complexes With Hdmopta and Dmoptamentioning
confidence: 85%
“…of Me(CF 3 nonane (HdmoPTA) when the dmoPTA was reacted with KOH in EtOH. The proton between both N CH3 atoms in 55 can be removed easily using a 0.01 M KOH water solution or tBuOK in MeOH at room temperature, which gives the option to the ligand to [45][46][47][48][49] coordinate a second metal through the N CH3 atoms. Nevertheless, in presence of protic solvents such as EtOH, MeOH or H 2 O, the ligand dmPTA suffers the elimination of the CH 2 group between the N CH3 atoms giving rise to the new HdmoPTA, which can be isolated as tetrafluoroborate salt by reaction with HBF 4 .…”
Section: Complexes With Hdmopta and Dmoptamentioning
confidence: 99%
“…Finally, the 31 P{ 1 H} NMR only showed the existence of one unique specie with phosphorus in dissolution with the expected signal pattern for the complex: a doublet for the PPh 3 ligand at δ = 37.39 ppm and a triplet at –15.10 ppm due to the dmoPTA ( 2 J PP = 39.2 Hz). Both signals arise at similar chemical shift than those for starting complex 2 (38.44; –13.94 ppm) with similar coupling constant (39.4 Hz) . The single‐crystal X‐ray diffraction structure of 4 showed that the asymmetric unit contains two OTf anions and two enantiomeric cationic Ru‐Zn complexes (Figure , Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The antiproliferative activity of the complex [RuCpCl(PPh 3 )(HdmoPTA‐1κ P )](CF 3 SO 3 ) ( 1 ) (the so‐called 1 st generation) against colon cancer cells was significant better (GI 50 = 1.7 µ m ) than that showed by cisplatin, that is currently used in anticancer therapy . The substitution of the chloride in 1 by one PPh 3 led to complex [RuCp(PPh 3 ) 2 (HdmoPTA‐1κ P )](CF 3 SO 3 ) 2 ( 2 ) (the so‐called first member of the 2 nd generation), which is more soluble in organic solvent, showing a substantial enhancement of the antiproliferative activity with respect to the starting complex 1 . Elimination of the HdmoPTA‐proton in 1 and further reaction with CoCl 2 provided the Ru‐Co complex [RuCp(PPh 3 ) 2 ‐µ‐dmoPTA‐1κ P :2κ 2 N , N′ ‐CoCl 2 ](CF 3 SO 3 ) ( 3 ) (the second member of the 2 nd generation), which showed a significant better antiproliferative activity than 1 (Figure ), despite Co II is not particularly known for its antimetastatic properties .…”
Section: Introductionmentioning
confidence: 99%
“…Ligands PTA, mPTA (N‐methyl‐1,3,5‐triaza‐7‐phosphaadamantane) and its derivative dmoPTA (3,7‐dimethyl‐1,3,7‐triaza‐5‐phosphabicyclo[3.3.1] nonane) have an adequate hydrophilic/hydrophobic balance to move through the biological system, which most of the times does not vary after coordination to metals. We obtained promising results with platinum, and ruthenium complexes containing the water soluble phosphane PTA and its derivative mPTA and noteworthy also with dmoPTA, which showed to be an excellent ligand to synthesise ruthenium complexes active against cis platin sensitive and resistant cell lines.…”
Section: Introductionmentioning
confidence: 90%